Effects of factors of self-regulation vs. factors of external regulation of learning in self-regulated study - Pachón-Basallo, Mónica; de la Fuente, Jesús; González-Torres, María C.; Martínez-Vicente, José Manuel; Peralta-Sánchez, Francisco J.; Vera-Martínez, Manuel M. (Frontiers in Psychology, 2022)
Since the mid-20th century, the study of Self-Regulated Learning has aimed to identify the distinctive characteristics that enable individuals to acquire new knowledge and skills under their control. The theory of Internal Self-Regulation vs. External Regulation in Learning (2017) has postulated that a large number of self-regulatory variables are mediated by regulated/non-regulated or dysregulated features of the context. After signing their informed consent, a total of 616 university students completed validated instruments of internal vs. external regulation in learning (SRL vs. ERL), behavioral regulation (SRB), regulatory teaching (RT), and metacognitive study control strategies (SRS). Using an ex-post facto design and correlation, regression, structural equation model and mediation analyses, the present research aimed to establish multicausal predictive relationships among the analyzed variables. Results indicated positive predictive effects between the external regulation variables on the self-regulation variables in learning (regulation (SRL)/non-regulation (NRL)/dysregulation (DRL)); as well as positive predictive effects between self-regulated learning (SRL) on behavioral self-regulation (SRB), regulatory learning (RT) and metacognitive study control strategies (SRS). Additionally, external regulation (ERL) not only predicted but mediated numerous relations among the variables studied. Other findings and important considerations for future research in the field of self-regulation are discussed.